A common mitochondrial DNA variant is associated with idiopathic dilated cardiomyopathy in two different populations - Khogali, S; Mayosi, B; Beattie, J; McKenna, W; Watkins, H; Poulton, J (2000)
Dilated Cardiomyopathy (DCM) is a devastating disease. It is a recognised manifestation of mitochondrial disease and in some cases the only clinical abnormality. Although specific mitochondrial DNA(mtDNA) mutations in tRNAleu/lle have been identified in mitochondrial disease associated with DCM, it is not known whether any mtDNA variants predispose to sporadic DCM. We aimed to determine the prevalence of a mtDNA variant (T16189C), in DCM; this variant has been previously implicated in susceptibility to type 2 diabetes and is thought to impair energy production. We screened leucocyte DNA from 24 non-diabetic Black South African DCM patients and 19 normal Black South African controls for the T16189C polymorphism. PCR amplification and sequencing of the D-loop segment was performed. Sequence analyses revealed a positive association of the 16189 polymorphism with DCM in this population. In order to test our hypothesis that this variant may itself play a pathogenic role in DCM, we investigated the prevalence of the same polymorphism in a different population of non-diabetic caucasian DCM patients with no family history. DNA extracted from leucocytes and cardiac biopsies from 93 DCM patients were analysed for the T16189C polymorphism by PCR and sequencing and the prevalence compared to that in 545 normal Caucasian European controls, previously analysed. Analysis of the T16189C polymorphism in the Black South African DCM patients and controls revealed that the polymorphism (with associated length variation) was present in 46% (11/24) compared with only 16% (3/19) of Black South African controls(p=0.036). Of the caucasian(UK) DCM patients, 17.2% (16/93) had the T16189C polymorphism compared with 8.8% (48/545) of controls (p=0.01; O.R.=2.15 [95% Cl 1.06-3.92]). As the T16189C variant has arisen in several distinct maternal lineages, this association is unlikely to be due to a founder effect. The association of the 16189 mtDNA variant with DCM in two different populations, and in different lineages, suggests that this variant may play a direct role in the pathogenesis of DCM. The critical position of nucleotide 16189 within the control region of mtDNA, is such that variations in this region may directly affect mitochondrial function. This is the first association of DCM with a common population polymorphism.